A five year financial plan for Rustan Marketing Specialists, Incorporated - Angelique Ginete, Enice D. Jimenez, Carl Vixen Magbitang, Patrick Jan Milo, Bryce Jenard Hernandez, Arabiah Lampa, Shean Christian Lopena and Ryzel Louiese Marzan. 4 0 16; 5
u
Financial Plan: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2